PIROLISIS LAMBAT OFF-GRADE RUBBER DENGAN REAKTOR PIROLISIS SEMI-KONTINYU PADA SUHU 200 oC - Mutiara Pertiwi; RR Dirgarini Julia Nurlianti Subagyono; Ari Susandy Sanjaya; Mohd. Asyraf Kassim (PROSIDING SEMINAR KIMIA, 2025)
Off-grade Rubber is a by-product from rubber industries that has potential as a renewable energy raw material. This study aims to determine the results of slow pyrolysis of off-grade rubber at a temperature of 200 oC using a laboratory-scale semi-continuous pyrolysis reactor for 30 minutes. The off-grade rubber had a moisture content of 23.62 ± 2.26% and an ash content of 11.24 ± 1.09%. The bio-oil yield and the aqueous phase yield at 200 oC were 0.27% and 2.1%, respectively. Chemical compound analysis using Gas Chromatography-Mass Spectrometry (GC-MS) showed five dominant compounds, namely glyceroltriethylether, 3,3-dimethyl-1-oxa-3-silacycloheptanone-7, 1-methylethyl heptanoate, 1-methyl-1-ethoxy-1-silacyclopentane, and heptanoic acid, 1-methylethyl ester. Keywords: Bio-oil, off-grade Rubber, Slow Pyrolysis